AB0118 MIR-29A and Messenger RNA Expression of Bone Turnover Markers in Canonical Wnt Pathway in Patients with Ankylosing Spondylitis. (15th July 2016) - Huang, J.; Song, G.; Yin, Z.; Fu, Z.; Ye, Z.
Abstract : Background: Recent studies showed that canonical Wnt pathway and miR-29a play important roles in the pathogenesis of bone formation. Objectives: We studied the levels of miR-29a and bone turnover markers in canonical Wnt pathway in ankylosing spondylitis (AS). Methods: The levels of miR-29a and mRNA of bone turnover markers in canonical Wnt pathway from peripheral blood mononuclear cells were determined by real-time quantitative polymerase chain reaction in 43 patients with AS and 42 healthy controls. Correlation analysis was conducted between the levels of miR-29a and mRNA and clinical measurements using Spearman's correlation test. Serum levels of components of canonical Wnt pathway including Dickkopf-1 (DKK-1), GSK-3β, β-catenin, alkaline phosphatase (ALP) and osteocalcin (OC) were detected using ELISA method. Results: Compared to healthy controls, the levels of miR-29a, Dickkopf (DKK)-1, β-catenin and Runx2 mRNA were significantly higher in AS patients (p<0.05). In contrast, the levels of Gsk-3βmRNA was significantly lower in AS patients than that in healthy controls (p<0.05). Gsk-3βmRNA was positively correlated withβ-catenin mRNA expression (p<0.05). Only DKK-1 mRNA expression was negatively correlated with disease course (p<0.05). No significant difference was observed between AS patients and healthy controls for the levels of GSK-3β, β-catenin, ALP and OC, respectively (p>0.05).The levels of DKK-1 was significantly higher in AS patients (1914.46±407.82 pg/ml) than that in healthy controls (1729.07±352.86 pg/ml) (p<0.05). There was no correlation between high DKK-1 level and any of the clinical parameters contributing to inflammation or bone formation. However, the correlation between OC and disease duration was significant in AS patients (r=0.323, p=0.034). Conclusions: The osteoblastic marker miR-29a and downstream mRNA of canonical Wnt signaling was upregulated in AS, suggesting their possible role in the new bone formation in AS. Alteration of bone turnover markers in canonical Wnt pathway was observed in AS. This might partially explain the complicated mechanism of bone formation in the disease. References: Corr M. Wnt signaling in ankylosing spondylitis. Clin Rheumatol. 2014;33(6):759–62. Uderhardt S, Diarra D, Katzenbeisser J, David JP, Zwerina J, Richards W, et al. Blockade of Dickkopf (DKK)-1 induces fusion of sacroiliac joints. Ann Rheum Dis 2010;69:592–7. Kapinas K, Kessler CB, Delany AM. miR-29 suppression of osteonectin in osteoblasts: regulation during differentiation and by canonical Wnt signaling. J Cell Biochem 2009;108:216–24. Kapinas K, Kessler C, Ricks T, Gronowicz G, Delany AM. miR-29 modulates Wnt signaling in human osteoblasts through a positive feedback loop. J Biol Chem 2010;285:25221–31. Huang J, Song G, Yin Z, Luo X, Ye Z. Elevated miR-29a expression is not correlated with disease activity index in PBMCs of patients with ankylosing spondylitis.Mod Rheumatol 2014;24:331–4. Acknowledgement: This research was supported by National Natural Science Foundation of China (81301529), Natural Science Foundation of Guangdong Province (S2013040012296), Shenzhen science and technology project (JCYJ20150331142757389) and Public Welfare Scientific Research Project of Futian District Shenzhen (FTWS201308). Disclosure of Interest: None declared